Global HIV‐1 transmitted drug resistance in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Baxter, JD; Dunn, D; White, E; Sharma, S; Geretti, AM; Kozal, MJ; Johnson, MA; Jacoby, S; Llibre, JM; Lundgren, J; ,
Abstract : Objectives: HIV‐1 transmitted drug resistance (TDR) in treatment‐naïve individuals is a well‐described phenomenon. Baseline genotypic resistance testing is considered standard of care in most developed areas of the world. The aim of this analysis was to characterize HIV‐1 TDR and the use of resistance testing in START trial participants. Methods: In the Strategic Timing of AntiRetroviral Treatment (START) trial, baseline genotypic resistance testing results were collected at study entry and analysed centrally to determine the prevalence of TDR in the study population. Resistance was based on a modified 2009 World Health Organization definition to reflect newer resistance mutations. Results: Baseline resistance testing was available in 1946 study participants. Higher rates of testing occurred in Europe (86.7%), the USA (81.3%) and Australia (89.9%) as compared with Asia (22.2%), South America (1.8%) and Africa (0.1%). The overall prevalence of TDR was 10.1%, more commonly to nonnucleoside reverse transcriptase inhibitors (4.5%) and nucleoside reverse transcriptase inhibitors (4%) compared with protease inhibitors (2.8%). The most frequent TDR mutations observed were M41L, D67N/G/E, T215F/Y/I/S/C/D/E/V/N, 219Q/E/N/R, K103N/S, and G190A/S/E in reverse transcriptase, and M46I/L and L90M in protease. By country, the prevalence of TDR was highest in Australia (17.5%), France (16.7%), the USA (12.6%) and Spain (12.6%). No participant characteristics were identified as predictors of the presence of TDR. Conclusions: START participants enrolled in resource‐rich areas of the world were more likely to have baseline resistance testing. In Europe, the USA and Australia, TDR prevalence rates varied by country.